Carbon pricing in the EU: Evaluation of different EU ETS reform options. (October 2016) - Brink, Corjan; Vollebergh, Herman R.J.; van der Werf, Edwin
Abstract: This paper studies various options to support allowance prices in the EU Emissions Trading System (ETS), such as adjusting the cap, an auction reserve price, and fixed and variable carbon taxes in addition to the EU ETS. We use a dynamic computable general equilibrium model that explicitly allows for allowance banking and for a detailed cost-effectiveness analysis at the EU Member State level. We find that tightening the cap provides an ad hoc solution to the fundamental issue of the robustness of the effective carbon price, while introducing a price component to the ETS brings structural carbon price support in times of negative demand shocks for emission allowances. These price-based policies still benefit from the intertemporal flexibility through the banking provision in the EU ETS by re-allocating emissions over time with stronger emission reductions in early years and emission increases in later years. A higher emission price has a larger negative impact on the new Member States' economies than on other Member States. Furthermore, introducing a carbon tax in addition to the EU ETS decreases the price of allowances, resulting in welfare gains for net buyers of allowances while net sellers are worse off. Highlights: We analyse reform options for European Union Emission Trading System (EU ETS) with a CGE model. Variable carbon tax and auction reserve price support carbon price at least cost. Price-based reforms decrease early emissions but increase later emissions through banking. New Member States' economies are affected more than others by higher CO2 prices. Lower allowance prices due to a carbon tax are unfavourable to net sellers of allowances.